2014
DOI: 10.1208/s12249-014-0169-9
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Drug Diffusion in Human Nails

Abstract: Abstract. The main objective of the current work is to demonstrate the process of passive lateral diffusion in the human nail plate and its effect on the passive transungual permeation of antifungal drug ciclopirox olamine (CPO). A water soluble dye, methyl red sodium salt (MR) was used to visualize the process of lateral diffusion using a novel suspended nail experiment. The decline in concentration of CPO correlates with that of concentration of MR from the proximal to the distal end of the nail in suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…For this, hoof samples were cut into small discs using an 8-mm punch and placed between two PTFE adapters with an O-shaped ring of 5 mm in diameter. The ratio between the area of the O-shaped ring and the bovine hoof samples was 0.392 and, therefore, in accordance with Palliyil et al [35], the lateral diffusion caused by the edge effect is not expected to have a significant influence on our results. The receptor compartment was filled with 5 mL of phosphate buffered saline (PBS, pH 7.4) and with 5% of HP-β-CD, and the cells were equilibrated at 37 • C in a water bath with magnetic stirring.…”
Section: Permeation Studysupporting
confidence: 91%
“…For this, hoof samples were cut into small discs using an 8-mm punch and placed between two PTFE adapters with an O-shaped ring of 5 mm in diameter. The ratio between the area of the O-shaped ring and the bovine hoof samples was 0.392 and, therefore, in accordance with Palliyil et al [35], the lateral diffusion caused by the edge effect is not expected to have a significant influence on our results. The receptor compartment was filled with 5 mL of phosphate buffered saline (PBS, pH 7.4) and with 5% of HP-β-CD, and the cells were equilibrated at 37 • C in a water bath with magnetic stirring.…”
Section: Permeation Studysupporting
confidence: 91%
“…To conduct diffusion experiments, we used two cylindrical PTFE adapters with an O-shaped ring of 0.5 cm diameter, giving an effective diffusion area of 0.196 cm 2 , and the bovine hoof slices used were 0.8 cm in diameter. Palliyil et al in 2014 [23] demonstrated the importance of the effect of the passive lateral diffusion of ciclopirox olamine in nail during in vitro permeation experiments. This work shows lateral diffusion can reduce the in vitro passive transungual drug permeation, and they highlight the importance of the relationship between the dimensions of the nail sample and the diffusional surface, recommending a nail just enough to cover the hole of the adapter.…”
Section: Resultsmentioning
confidence: 99%
“…Topical treatments are usually recommended over systemic treatments due to i) drug-drug interactions, ii) counter indications, and iii) a low drug concentration at the nail bed requiring too high doses of the systemic drug [5,14]. Therefore, determining the permeability of the nail plate and enhancing it have been topics of research conducted by formulation scientists and biophysicists in recent years [15][16][17][18][19][20][21]. Active substances, including relatively large molecule antifungals [20,22], and smaller entities, such as plasma-generated NO 2 [23], have been successfully delivered through keratinized surfaces by various methods.…”
Section: Introductionmentioning
confidence: 99%